FORMS OF NARITVA IN “KANTHAPURA” (Journal of Namibian Studies : History Politics Culture, 2023)
Kanthapura, a microcosm of India, represents women as both the physical and spiritual center of villagers' lives, showcasing them not only as socio-cultural leaders but also as political embodiments of 'Shakti'. The novel explores the world of women, delving into traditional 'jayanti' ceremonies and the innate wisdom of grandmothers as they narrate the 'Sthalapurana'. The intellectually curious reader is granted insight into the minds of Indian women, replete with positive emotions. This paper aims to highlight the presence of empowered, multitasking women throughout history, and how contemporary women have inherited and demonstrated this consciousness across various domains.